The Upregulation of Trophinin-Associated Protein (TROAP) Predicts a Poor Prognosis in Hepatocellular Carcinoma - Hu, Hao (J Cancer, 2019)
Purpose: Trophinin-associated protein (TROAP) is a cytoplasmic protein that plays a significant role in the processes of embryo transplantation and microtubule regulation. However, the relevant survival analysis and cancer progression analysis have not yet been reported. Methods: Eighteen matched pairs of tumor and adjacent non-tumor samples were evaluated to detect the TROAP mRNA level. Immunohistochemistry (IHC) was used to evaluate the TROAP expression in 108 hepatocellular carcinoma patients who underwent surgical resection. Meanwhile, data from the TCGA database was statistically evaluated. Results: In the present study, we detected a significant increase in the TROAP mRNA level in tumor tissues when compared with adjacent non-tumor tissues. Moreover, the upregulation of TROAP was associated with increased serum AFP and GGT; the greater the tumor number was, the larger the tumor size, differentiation grade, and cancer embolus in clinical analysis. In HCC patients, elevated TROAP expression in the primary tumor was positively related to clinical severity, such as poor overall survival and disease-free survival. In addition, both univariate and multivariate survival analysis validated that TROAP expression was a promising independent risk factor for overall survival and disease-free survival in HCC patients. Furthermore, the results derived from the analysis of data from the TCGA database were consistent with previous results. Altogether, our results show that TROAP is a novel crucial regulator of HCC progression and is a potential therapeutic biomarker for HCC patients. Conclusions: Elevated TROAP expression predicted a poor prognosis, and TROAP may serve as a potential biomarker for application in oncotherapy.